IDENTIFIKASI DAYA TARIK SOSIAL MEDIA INFLUENCER TASYA FARASYA - Dwi Feni Aiman (Universitas Mercu Buana, 2020)
Social media influencer as a strategy that markets products, with a variety of social media platforms such as Instagram, YouTube, Facebook and other social media, social media influencers provide Brands to market and advertise directly to their target audience. There are several influencers that have been categorized according to the skills or concepts they made from the beginning, such as beauty influencers, influencers whose concept of beauty. Through reviews given by social media influencers will add value to the Brand's credibility and increase public awareness of the Brand so that the public can use the value of the service or product offered to a personal level. This study discusses how to increase the appeal possessed by one of the beauty influences, namely Tasya Farasya in supporting a